HAMBATAN PENEGAKAN HUKUM TERHADAP PELAKU KEJAHATAN KORPORASI DALAM SISTEM PERADILAN PIDANA INDONESIA: (Menunggu Peran Mahkamah Konstitusi dalam Upaya Pemberantasan Kejahatan Korporasi) - Zulkarnain, Zulkarnain Zulkarnain (Jurnal Konstitusi, 2011)
Corporate crime is an extra ordinary crime that should be fought against with great efforts. Such efforts, however, are inversely proportional to the policies in the criminal laws serving as a base for their enforcement. This present research would focus on three problems, namely the criminalization of the corporate crime in Indonesia, the system of corporate responsibility adopted, and the concept of the system of corporate responsibility that will be applied. The research results showed that the criminalization in all forms of corporate crimes, according to the positive criminal law in Indonesia, was recognized as crimes. However, the arrangement between one criminal code and the others varies. The system of the criminal responsibility adopted in the positive law in Indonesia tends towards the identification and delegation theories where those who do the mistakes and the source of authorities they possess would be examined. However, comprehensively, the stipulations in one criminal law and the others are different. In the draft of Indonesia Criminal Code, it is not explicitly stated that the criminal would be condemned, so that it can be interpreted that the criminal should not be responsible for the crime he does since the criminal responsibility has been moved to the corporation.